Resolving the species status of overlooked West‐Palaearctic bumblebees. (27th March 2021) - Brasero, Nicolas; Ghisbain, Guillaume; Lecocq, Thomas; Michez, Denis; Valterová, Irena; Biella, Paolo; Monfared, Alireza; Williams, Paul Hugh; Rasmont, Pierre; Martinet, Baptiste
Abstract: Multisource approaches in taxonomy gather different lines of evidence in order to draw strongly supported taxonomic conclusions and constitute the basis of integrative taxonomy. In the case of overlooked taxa with disjunct distributions for which sampling is more challenging, integrative approaches help to propose stable hypotheses at the species and subspecies levels. Here, based on genetic and semio‐chemical traits, we performed an integrative taxonomic analysis to evaluate species delimitation hypotheses within a monophyletic group of bumblebees (Hymenoptera, Apidae, Bombus ) including the formerly recognised subgenera Eversmannibombus, Laesobombus and Mucidobombus which are now included in the subgenus Thoracobombus . Our results demonstrate the conspecificity of several polytypic taxa, and we formally recognise the subspecies Bombus laesus aliceae comb. nov. Cockerell, 1931, endemic to North Africa, based on its allopatry, unique mitochondrial haplotype and divergent cephalic labial gland secretions. This highlights the need to maintain studying polytypic complexes of bumblebee taxa for which phylogenetic relationships could be still entangled and eventually implement conservation strategies for taxonomically differentiated lineages.